First record of Leptus sp. (Latreille) (Acari: Erythraeidae) parasitizing horse fly (Diptera: Tabanidae) from Marambaia Island, Mangaratiba, Rio de Janeiro, Brazil - Guimaraes, Ronald Rodrigues; Guimarães-Júnior, Ronald Rodrigues; Storti Rodrigues, Harlan Ronald; Guimarães, Roney Rodrigues; Carvalho, Raimundo Wilson (EntomoBrasilis, 2019)
Abstract. This scientific note refers to the first record of a larvae of mite of genus Leptus (Acari: Erythraeidae) found parasitizing a specimen of horsefly (Diptera: Tabanidae) on Marambaia Island, Mangaratiba, Rio de Janeiro, Brazil. Primeiro registro de Leptus sp. (Latreille) (Acari: Erythraeidae) parasitando mutuca (Diptera: Tabanidae) da Ilha da Marambaia, Mangaratiba, Rio de Janeiro, Brasil Resumo. Esta nota científica se refere ao primeiro registro de uma larva de ácaro do gênero Leptus (Acari: Erythraeidae) encontrada parasitando um espécime de mutuca(Diptera: Tabanidae) na Ilha de Marambaia, Mangaratiba, Rio de Janeiro, Brasil.